Epidemiology, Risk Factors, and Prevention Strategies for Neonatal Sepsis: A Review - Nikita; Payal, Nikhil; Bedi, Nidhi; Sharma, Mukesh; Khandait, Manisha (Archives of Clinical and Biomedical Research, 2025)
Systemic invasion of pathogenic microorganism during the neonatal period causing inflammatory response is referred to as neonatal sepsis. Sepsis is one of the main causes for neonatal mortality and morbidity all over the globe, predominately in the middle- and low-income countries due to improper infection control procedures and inconsistent hygiene habits. Clinical features of sepsis in neonates are non-specific compared to children and adults making timely diagnosis challenging. This review emphasizes the contributing factors epidemiological trends, and pathogenic mechanisms associated with neonatal sepsis. On the basis of manifestation of clinical symptoms neonatal sepsis is categorized into two groups, Early onset of sepsis (EOS) <72hr and late onset of sepsis (LOS) >72hr. In high income countries both EOS and LOS have distinct causative agents and risk profiles while the EOS is supposed to be primarily caused due to maternal risk factors such as chorioamnionitis, preterm labor, and prolonged rupture of membrane while LOS is associated with hospital acquired infections exacerbated by inadequate infection control measures in healthcare settings. The critical need for improved prenatal care, stringent infection control protocols, and effective antibiotic stewardship to mitigate the incidence of neonatal sepsis. Additionally, disparities in healthcare infrastructure are highlighted as barriers to effective management and prevention.